A case report of Ramsay Hunt syndrome - Carriço, Carla (2011)
A CASE REPORT OF RAMSAY HUNT SYNDROME Although earache is a common symptom in General practice, this case report aims to alert the reader to a rare cause of earache. The Ramsay Hunt syndrome is a rare complication of herpes zoster infection. Its clinical features are peripheral facial paralysis and vesicular lesions of the ear or mouth. We report the case of a woman who came to a consultation with her family doctor with a three day history of a burning sensation in her right ear. The following day she had a right-sided facial paralysis and vesicular lesions in the right ear. The diagnosis of Ramsay Hunt syndrome was made. Ramsay Hunt syndrome is the second most common cause of non-traumatic peripheral facial paralysis. The diagnosis is clinical and is made in the presence of pain, vesicular lesions, lacrimation, nasal congestion, salivation and peripheral facial paralysis. The main complications are encephalitis, myelitis and cranial and peripheral nerve palsies. The largest retrospective study published to date showed benefit from early treatment with acyclovir and prednisolone. The prognosis is good and 75% of all patients have a full recovery in one week.